Design, fabrication and testing of a urea super granule applicator - N. A. SAKKEENA DEEVI; K. P. Sudheer; Er. Jippu Jacob (Guide) (Tavanur 1993 Department of Farm Power Mach!nery and Energy)
Design, fabrication and testing of a urea super granule applicator
Design, fabrication and testing of a urea super granule applicator